Plasma and rectal mucosal oxylipin levels during aspirin and eicosapentaenoic acid treatment in the seAFOod polyp prevention trial. (May 2023) - Fuller, H.; Race, A.D.; Fenton, H.; Burke, L.; Downing, A.; Williams, E.A.; Rees, C.J.; Brown, L.C.; Loadman, P.M.; Hull, M.A.
Highlights: RvE1 and 15-epi-LXA4 were not detectable (>20 pg/ml). 18-HEPE and 15-HETE were present in ng/ml amounts in plasma. EPA treatment was associated with increased levels of 18-HEPE. 18-HEPE levels did not predict colorectal polyp risk reduction by EPA. Abstract: Background: Aspirin and eicosapentaenoic acid (EPA) have colorectal polyp prevention activity, alone and in combination. This study measured levels of plasma and rectal mucosal oxylipins in participants of the seAFOod 2 × 2 factorial, randomised, placebo-controlled trial, who received aspirin 300 mg daily and EPA 2000 mg free fatty acid, alone and in combination, for 12 months. Methods: Resolvin (Rv) E1, 15-epi-lipoxin (LX) A4 and respective precursors 18-HEPE and 15-HETE (with chiral separation) were measured by ultra-high performance liquid chromatography-tandem mass spectrometry in plasma taken at baseline, 6 months and 12 months, as well as rectal mucosa obtained at trial exit colonoscopy at 12 months, in 401 trial participants. Results: Despite detection of S - and R - enantiomers of 18-HEPE and 15-HETE in ng/ml concentrations, RvE1 or 15‑epi-LXA4 were not detected above a limit of detection of 20 pg/ml in plasma or rectal mucosa, even in individuals randomised to both aspirin and EPA. We have confirmed in a large clinical trial cohort that prolonged (12 months) treatment with EPA is associated with increased plasma 18-HEPE concentrations (median [inter-quartile range] total 18-HEPE 0.51 [0.21–1.95] ng/ml at baseline versus 0.95 [0.46–4.06] ng/ml at 6 months [ P <0.0001] in those randomised to EPA alone), which correlate strongly with respective rectal mucosal 18-HEPE levels ( r = 0.82; P <0.001), but which do not predict polyp prevention efficacy by EPA or aspirin. Conclusion: Analysis of seAFOod trial plasma and rectal mucosal samples has not provided evidence of synthesis of the EPA-derived specialised pro-resolving mediator RvE1 or aspirin-trigged lipoxin 15‑epi-LXA4 . We cannot rule out degradation of individual oxylipins during sample collection and storage but readily measurable precursor oxylipins argues against widespread degradation.